Flagellar rotor protein FliG is involved in the virulence of avian pathogenic Escherichia coli. (November 2021) - Yin, Lei; Shen, Xuehuai; Zhang, Danjun; Zhao, Ruihong; Dai, Yin; Hu, Xiaomiao; Zhou, Xueli; Hou, Hongyan; Pan, Xiaocheng; Qi, Kezong
Abstract: Avian pathogenic Escherichia coli (APEC), a type of extraintestinal pathogenic E. coli, causes avian colibacillosis, a disease of significant economic importance to poultry producers worldwide, which is characterized by systemic infection. However, the pathogenesis of avian pathogenic E. coli strains is not well defined. Here, the role of a flagellar rotor protein encoded by the fliG gene of avian pathogenic E. coli strain AE17 was investigated. To study the role of FliG in the pathogenicity of APEC, fliG mutant and complemented strains were constructed and characterized. The inactivation of fliG had no effect on APEC growth, but significantly reduced bacterial motility. Compared with the wild type, the fliG mutant was highly attenuated in a chick infection model and showed severe defects in its adherence to and invasion of chicken embryo fibroblast DF-1 cells. The fliG mutant also showed reduced resistance to serum in chicks. The expression of the inflammatory cytokines interleukin 1β (IL1β), IL6, and IL8 was reduced in HD-11 macrophages infected with the fliG mutant strain compared with their expression in the wild-type strain. These results demonstrate that the FliG contributes to the virulence of APEC. Highlights: This is the first report demonstrating that the role of FliG in the virulence of APEC. We identified that fliG affects its subversion of the host inflammatory response. The results will help to further elucidate the pathogenic mechanism employed by the APEC to devise strategies for therapy.